Ketahanan Kayu terhadap Serangan Rayap Tanah dengan Perlakuan Garam Metal The Subterranean Termites Resistance of Metal-Salt Treated Wood - Sulaeman Yusuf; Takeshi Furuno (Jurnal Ilmu dan Teknologi Kayu Tropis, 2005)
Treatment of wood with a boron compound (inorganic substance) having both fire and biological resistance, dimensional stability and other features has been studied. In this experiment, borax and metal-salt treated wood were studied to evaluate the termite resistance. The water-saturated wood specimens were first impregnated by a saturated borax solution and then diffuse-penetrated with Zn and Cu. The second specimens were impregnated with colloidal silica and evaluated the effect of wood treatment by subterranean termites.The results indicated that colloidal-silica and methaborate-salt showed generally good termite resistance with negligible mass loss of specimens